2016
DOI: 10.1111/epi.13652
|View full text |Cite
|
Sign up to set email alerts
|

WONOEP appraisal: Biomarkers of epilepsy‐associated comorbidities

Abstract: Neurologic and psychiatric comorbidities are common in patients with epilepsy. Diagnostic, predictive, and pharmacodynamic biomarkers of such comorbidities do not exist. They may share pathogenetic mechanisms with epileptogenesis/ictogenesis, and as such are an unmet clinical need. The objectives of the subgroup on biomarkers of comorbidities at the XIII Workshop on the Neurobiology of Epilepsy (WONOEP) were to present the state-of-the-art recent research findings in the field that highlighting potential bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 80 publications
1
28
0
Order By: Relevance
“…Breathing pattern was investigated at P100 using plethysmography and revealed no difference between heterozygous knock‐in and WT animals for all measured parameters (mean frequency, hyperventilation, apnea, tidal volume, and respiratory rate; n = 10 Kcnq2 +/+ mice and n = 11 K cnq2 Thr274Met/+ mice; Figure ). We also investigated the presence of stereotypies in the two groups using the marble‐burying test because of the unusual rate of stereotypy in patients with epilepsies 12,13. The test quantifies repetitive and perseverating behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Breathing pattern was investigated at P100 using plethysmography and revealed no difference between heterozygous knock‐in and WT animals for all measured parameters (mean frequency, hyperventilation, apnea, tidal volume, and respiratory rate; n = 10 Kcnq2 +/+ mice and n = 11 K cnq2 Thr274Met/+ mice; Figure ). We also investigated the presence of stereotypies in the two groups using the marble‐burying test because of the unusual rate of stereotypy in patients with epilepsies 12,13. The test quantifies repetitive and perseverating behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, endothelial cells displayed marked ADK immunoreactivity ( Figure 1H) within the damaged hemosphere. associated with epilepsy are crucial to improve the quality of life in patients with epilepsy [7].…”
Section: Overexpression Of Adk In Rementioning
confidence: 99%
“…Therefore, treatment of comorbidity associated with epilepsy could contribute to the therapeutic effect of epilepsy and improve the quality of life. More than one third of patients with epilepsy are pharmacoresistant [2][3][4], and apart from those who are candidates for resective surgery, most patients will continue to suffer recurrent seizures and comorbidities comprising of neurologic, cognitive and psychiatric symptoms [5][6][7][8]. Therefore, novel solid biomarkers for the prediction, diagnosis, and treatment of epilepsy and comorbidities Review Tianfu Li pathological hallmark in patients with pharmacoresistant epilepsy caused by a wide range of neurodegenerative conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides severity assessment, the data generated in the different epilepsy animal models can be used to gain further insight into psychiatric comorbidities of epilepsy and the respective face validity of different animal models. Studies have demonstrated the existence of psychiatric comorbidities in patients, with matching behavioral alterations seen in rodent epilepsy models . However, previous findings were not always consistent and robust, so that a comprehensive analysis of behavioral alterations in different epilepsy models under identical conditions is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the existence of psychiatric comorbidities in patients, with matching behavioral alterations seen in rodent epilepsy models. [13][14][15] However, previous findings were not always consistent and robust, [16][17][18] so that a comprehensive analysis of behavioral alterations in different epilepsy models under identical conditions is of particular interest.…”
Section: Introductionmentioning
confidence: 99%